Citra Perempuan dalam Novel Perempuan Yang Menunggu Di Lorong Menuju Laut karya Dian Purnomo: Kajian Feminisme - Fajri, Lisa Nur; Zulfadhli (Universitas Negeri Padang, 2024)
This study aims to describe the image of the main character of women contained in the novel Perempuan yang Menunggu di Lorong Menuju Laut. The type of research used is literary research with descriptive method. The data source is the novel Perempuan yang Menunggu di Lorong Menuju Laut published in 2023 by Dian Purnomo. The data collection technique in this research is a literature study, namely (1) understanding the content of the story and the meaning of the novel under study, (2) conducting literature studies, namely reading and recording things related to research objectives (3) collecting related to the formulation of research problems into tables. The data analysis techniques in this research are: (1) classifying data regarding the form of women's image contained in the novel (2) describing and analyzing the context of speech that describes the image of women in the novel under study (3) interpreting data, (4) drawing conclusions and reporting the results of data analysis. The results of this study explain that the image of women contained in the novel Perempuan yang Menunggu di Lorong Menuju Laut includes women's self-image and women's social image. (a) Women's self-image consists of women's physical image and women's psychological image. (b) The social image of women includes: the role of women in the family and society. The image of women formed in the novel is progressive because it does not follow the conventions of the ideal image of women according to patriarchal ideology.